Current Concepts in Arm Care Exercise Programs and Injury Risk Reduction in Adolescent Baseball Players: A Clinical Review. (May 2021) - Matsel, Kyle A.; Butler, Robert J.; Malone, Terry R.; Hoch, Matt C.; Westgate, Philip M.; Uhl, Tim L.
Context: Awareness of important injury risk factors associated with excessive pitching volume has been highlighted in the literature, but injury rates remain high. Shoulder pain in baseball players is associated with various changes in musculoskeletal movements, which presents as measurable impairments throughout the kinetic chain. Baseball coaches and rehabilitation professionals have utilized exercise programs targeting strength and flexibility of the throwing arm to prevent injuries. The purpose of this review is to summarize the current evidence regarding the effectiveness of arm care exercise programs in reducing upper extremity injury rates in adolescent baseball players. Evidence Acquisition: A search of electronic databases, including CINAHL with full text, MEDLINE, and SPORTDiscus was conducted to retrieve available articles in English from the years 2010 through 2020. The search terms injury prevention, exercise, and adolescent baseball were used. Study Design: Clinical review. Level of Evidence: Level 4. Results: Improving shoulder internal rotation range of motion by stretching the posterior shoulder muscles daily was associated with a 36% risk reduction of shoulder and elbow injuries. Group-based arm care exercise programs that target multiple musculoskeletal impairments demonstrated an approximately 50% reduced risk of elbow injury. Conclusion: For adolescent baseball players, arm care injury prevention programs focusing on important musculoskeletal impairments are effective at reducing injury incidence rates. Multimodal injury prevention programs that improve multiple musculoskeletal impairments are more comprehensive and may result in better injury reduction than programs focusing on a singular impairment.